Electrochemical Study of Diphenyl Ether Derivatives Used as Herbicides - Amira Zaouak; Fatma Matoussi; Mohamed Dachraoui (International Journal of Electrochemistry)
The electrochemical behaviour of five nitro diphenyl ethers used as herbicides is investigated in acetonitrile. A detailed study by cyclic voltammetry and exhaustive electrolysis is carried out for the anodic oxidation of 2-Chloro-6-nitro-3-phenoxyaniline (aclonifen) and shows that the major oxidation product is a dimeric compound. A mechanistic scheme involving a coupling process is postulated for the electrochemical oxidation of this compound. Furthermore, the use of differential pulse voltammetry on a glassy carbon electrode permits the selective determination of aclonifen. The limit of detection is 0.6 μg/mL.